Maya's notebook [compact disc, unabridged] : a novel - Allende, Isabel (Harper Audio, 2013)
Maya, a young American on the run, is sent to Chiloé, in a remote part of Chile, her grandmother's homeland, where she records in her diary her adjustment to a new country, her drug problems, her romantic life, and other developments.